2014
DOI: 10.1080/00224545.2014.953024
|View full text |Cite
|
Sign up to set email alerts
|

Unanswered Prayers: Religiosity and the God-Serving Bias

Abstract: Two self-report experiments examined how religiosity affects attributions made for a target person's death. Online adults (Study 1, N = 427) and undergraduate students (Study 2, N = 326) read about Chris who had a heart attack, used religious or health behaviors, and lived or died. Participants made attributions to Chris and God (both studies), and reported their emotions (Study 2). Participants made more attributions to Chris when he lived than when he died, but only when he used health behaviors. The highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(34 citation statements)
references
References 69 publications
5
29
0
Order By: Relevance
“…Appraisal theories propose that emotions arise as a result of cognitive interpretations of events along dimensions such as goal relevance, goal congruence, certainty, coping potential, and agency (Moors, Ellsworth, Scherer, & Frijda, ), with the nature and valence of the emotion being determined by the pattern of appraisal. Religious and spiritual beliefs seem to have important effects on the appraisal process, with religious individuals often invoking divine causation or purpose when appraising a significant life event (Pargament et al, ), especially when those events are positive and life‐altering (Lupfer, Tolliver, & Jackson, ; Riggio, Uhalt, & Matthies, ). Such benevolent appraisals are predictive of positive mental health outcomes (Pargament, Koenig, Tarakeshwar, & Hahn, ), and it is likely that attenuation of negative emotions and promotion of positive emotions play a significant role in this process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Appraisal theories propose that emotions arise as a result of cognitive interpretations of events along dimensions such as goal relevance, goal congruence, certainty, coping potential, and agency (Moors, Ellsworth, Scherer, & Frijda, ), with the nature and valence of the emotion being determined by the pattern of appraisal. Religious and spiritual beliefs seem to have important effects on the appraisal process, with religious individuals often invoking divine causation or purpose when appraising a significant life event (Pargament et al, ), especially when those events are positive and life‐altering (Lupfer, Tolliver, & Jackson, ; Riggio, Uhalt, & Matthies, ). Such benevolent appraisals are predictive of positive mental health outcomes (Pargament, Koenig, Tarakeshwar, & Hahn, ), and it is likely that attenuation of negative emotions and promotion of positive emotions play a significant role in this process.…”
Section: Introductionmentioning
confidence: 99%
“…Our adoption of EMA also enabled us to improve the representativeness of the experiences we assessed. Previous research examining the effects of religion on interpretation of events has usually focused on major, life‐altering events, such as a heart attack (Riggio et al, ), moving to a new city (Lupfer et al, ), or the breakdown of a relationship (Ray, Lockman, Jones, & Kelly, ), and has generally found that religious individuals invoke religious or teleological explanations when attributing causality. In the present research, we sought to extend this line of reasoning to more mundane events, investigating whether religious individuals truly see divine influence in their daily lives, and whether this affects their experience of both positive emotions and resultant well‐being.…”
Section: Introductionmentioning
confidence: 99%
“…Our adoption of EMA also enabled us to improve the representativeness of the experiences we assessed. Previous research examining the effects of religion on interpretation of events have usually focused on major, life-altering events, such as a heart attack (Riggio et al, 2014), moving to a new city (Lupfer, Tolliver, & Jackson, 1996), or the breakdown of a relationship (Ray, Lockman, Jones, & Kelly, 2015), and have generally found that religious individuals invoke religious or teleological explanations when attributing causality. In the present research we sought to extend this line of reasoning to more mundane events;…”
Section: Examining Religion In Everyday Lifementioning
confidence: 99%
“…Appraisal theories propose that emotions arise as a result of cognitive interpretations of events along dimensions such as goal relevance, goal congruence, certainty, coping potential, and agency (Moors, Ellsworth, Scherer, & Frijda, 2013), with the nature and valence of the emotion being determined by the pattern of appraisal. Religious and spiritual beliefs seem to have important effects on appraisal process, with religious individuals often invoking divine causation or purpose when appraising a significant life event (Pargament, Olsen, Reilly, Falgout, Ensing, & Van Haitsma, 1992), especially when those events are positive and life-altering (Lupfer, Tolliver, & Jackson, 1996;Riggio, Uhalt, & Matthies, 2014). Such benevolent appraisals are predictive of positive mental health outcomes (Pargament, Koenig, Tarakeshwar, & Hahn, 2004), and it is likely that attenuation of negative emotions and promotion of positive emotions plays a significant role in this process.…”
Section: Introductionmentioning
confidence: 99%
“…We examine participant religious identification as a moderator. Based on social identity theory (Tajfel & Turner, 2004) and previous research (Lupfer et al, 1994(Lupfer et al, , 1996Riggio et al, 2014), we hypothesize that individuals identifying as Christian will make more attributions to God and religious processes (prayer, faith in God, worship of God) than individuals identifying as agnostic or atheist (Hypothesis 1). Based on social identity theory (Tajfel & Turner, 2004), self-serving bias (Anderson et al, 1996), and research indicating defensive processing of information threatening to group beliefs (Riggio, 2008), we predict that religious individuals will make more attributions to God and religious processes, but only when no Explaining Death by Tornado one is killed.…”
Section: The Current Studymentioning
confidence: 99%